Regulation of the mitotic activity of root meristems and growth processes of soybean seedlings with a contrasting photoperiodic response by selective light - Batuieva, Y.; Avksentieva, O. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2022)
The present paper concerns the influence of selective light irradiation of various spectrums ‒ red (RL, 660 nm), green (GL, 530 nm), and blue (BL, 450 nm) on the proliferative activity of root meristem cells, biomass accumulation, and growth processes in the above-ground and underground parts of etiolated soybean seedlings. Seedlings of the soybean (Glycine max (L.) Merr.) of two varieties, contrasting in photoperiodic reaction, the short-day variety Khadzhibei and the photoperiodic-neutral variety Yatran, were used as plant material. Sterilized soybean seeds were germinated in Petri dishes for three days in darkness at 22±1°C. After that, their photoreceptor system was activated by irradiation with monochromatic light of red, green, and blue spectrums for five days, 30 minutes daily, with the use of Korobov LED matrices. Control plants were cultivated under the same conditions but without selective light exposure. Samples for the proliferative activity analysis were taken in dynamics on the 6th, 7th, and 8th days of the experiment. The seedlings’ growth reaction was analyzed at the end of the experiment, on the 11th day. The experiments showed that axial organs of soybean seedlings react in different ways when exposed to selective light of various spectrums: linear measures of the seedlings’ above-ground part largely depend on the RL impact, while the root system reacts more actively to the BL impact. Under activation of the phytochrome system with RL, the above-ground part of seedlings changes its morphogenetic development program from scotomorphogenesis to photomorphogenesis. At the same time, biomass accumulation in the etiolated seedlings of the short-day Khadzhibey variety was influenced by irradiation with all the applied spectra; the biomass of photoperiodic-neutral soybean seedlings of the Yatran variety was affected only by RL. The root meristem of etiolated soybean seedlings of the Khadzhibey variety was sensitive to both RL and BL irradiation, while that of the seedlings of the Yatran variety reacted to a greater extent to the BL and GL exposure. Based on the results obtained, we suppose that soybean seedlings with contrasting photoperiodic sensitivity have different compositions and activity of photoreceptor systems. It is manifested in regulation of the meristem proliferative activity, growth, and morphogenetic processes.